Provisional Agenda for the Twenty-Eighth Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2013)
The following is the provisional agenda for the Twenty-Eight Meeting of the International Monetary and Financial Committee, which is to be convened at the IMF's Headquarters in Washington, D.C. on October 12, 2013.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Policy Agenda; Policy Coherence; PP